Acrylate resin, preparation method thereof and UV viscosity-reducing adhesive tape
By using UV adhesive tape prepared with materials such as acrylate resin and polyurethane oligomer of specific ratios, the problems of insufficient adhesive strength and degumming in the prior art are solved, and high adhesive strength and low peel strength are achieved Effect.
Patent Information
- Application Number
- CN202411541614.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing UV adhesive tapes are insufficient in the process of cutting or use and are prone to degumming, which cannot meet the high adhesion requirements for semiconductor cutting and hard material cutting.
Acrylate resin with specific ratios, including soft monomers, hard monomers and functional monomers, is prepared by polymerization, combining polyurethane oligomers, heat curing agents and photoinitiators to form UV detoxification with high adhesion adhesive tape.
The UV adhesive tape has high adhesion strength (greater than 35N/25mm) before lighting, and the peeling strength is significantly reduced after lighting, avoiding degumming problems and meeting the needs of high adhesion.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of advanced material technology, and in particular to an acrylic resin and a preparation method thereof, and a UV anti-viscosity tape. Background Art
[0002] UV adhesive tape is a tape that has high adhesion before light exposure, but greatly reduces adhesion after light exposure. It is widely used in medical, display, semiconductor and other fields due to its excellent transparency and adhesion. After a short period of light exposure, an interpenetrating polymer network structure is formed inside the UV adhesive tape. This structure changes the fluidity, cross-linking density, free volume and surface energy of the system, thereby reducing the adhesiveness and peeling strength of the tape.
[0003] In recent years, with the development of semiconductor cutting and cutting of hard materials such as glass and substrates, new demands have been put forward for UV adhesive tapes. UV adhesive tapes need to have a higher adhesion (for example, greater than 35N / 25mm) during cutting or use, but the UV adhesive tapes on the market have problems such as insufficient adhesion (generally around 20N / 25mm) and debonding. Summary of the invention
[0004] In view of this, the present application provides an acrylic resin and a preparation method thereof, and a UV anti-viscosity tape, aiming to improve at least one of the above technical problems.
[0005] In a first aspect, an embodiment of the present application provides an acrylate resin, wherein the synthetic raw materials of the acrylate resin include a soft monomer, a hard monomer and a functional monomer; the functional monomer includes hydroxyethyl acrylate, acrylamide and acrylic acid;
[0006] Among them, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9).
[0007] In some embodiments of the present application, the functional monomer consists of hydroxyethyl acrylate, acrylamide and acrylic acid; and / or
[0008] The synthetic raw materials of the acrylic resin also include an initiator. By mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid: the initiator is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9): (0.01-0.05).
[0009] In some embodiments of the present application, the glass transition temperature of the acrylic resin is -40 to -15°C; and / or
[0010] The relative molecular mass of the acrylic ester resin is 3500000-700000 g / mol.
[0011] In some embodiments of the present application, the solid content of the acrylic resin is 35-50%.
[0012] In some embodiments of the present application, the soft monomer includes at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate, and ethyl acrylate; and / or
[0013] The hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile; and / or
[0014] The initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, and ammonium persulfate.
[0015] The embodiment of the present application provides an acrylate resin, the molecular chain structure of the acrylate resin includes a soft monomer structural unit, a hard monomer structural unit and a functional monomer structural unit, the functional monomer structural unit includes a hydroxyethyl acrylate structural unit, an acrylamide structural unit and an acrylic acid structural unit, the soft monomer structural unit: the hard monomer structural unit: the hydroxyethyl acrylate structural unit: the acrylamide structural unit: the acrylic acid structural unit is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9). It should be noted that the acrylate resin in the embodiment of the present application is prepared by polymerization reaction of soft monomers, hard monomers and functional monomers, and accordingly, the soft monomers form the soft monomer structural units on the molecular chain structure of the acrylate resin after polymerization reaction, the hard monomers form the hard monomer structural units on the molecular chain structure of the acrylate resin after polymerization reaction, and the functional monomers form the functional monomer structural units on the molecular chain structure of the acrylate resin after reaction.
[0016] A second aspect of the present application provides a method for preparing an acrylate resin, the preparation method comprising the following steps:
[0017] Passing protective gas into the reaction vessel;
[0018] Adding part of the monomer raw material into the reaction container, and heating it to 65-70° C. to obtain a first reaction solution;
[0019] The first reaction liquid is further heated to 70-75° C., and the remaining monomer raw materials and a portion of the initiator are added and reacted for 1 to 2 hours to obtain a second reaction liquid;
[0020] The second reaction liquid is further heated to 75-85° C., and the remaining initiator is added to obtain an acrylic resin after the monomer raw materials react. The monomer raw materials include soft monomers, hard monomers and functional monomers. The functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid. By mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid: the initiator is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9): (0.01-0.05).
[0021] In some embodiments of the present application, the soft monomer includes at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate, and ethyl acrylate; and / or
[0022] The hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile; and / or
[0023] The initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, and ammonium persulfate.
[0024] A third aspect of the present application provides a UV anti-viscosity tape, wherein the UV anti-viscosity tape comprises the acrylic resin.
[0025] In some embodiments of the present application, the UV anti-viscosity tape includes a substrate film and a UV anti-viscosity adhesive located on the substrate film, and the UV anti-viscosity adhesive includes the acrylate resin, the thermal curing agent, the photoinitiator and the polyurethane polymer. By mass, the acrylate resin: the polyurethane polymer: the thermal curing agent: the photoinitiator is (60 to 80): (18 to 38): (0.5 to 1): (0.8 to 1.8).
[0026] In some embodiments of the present application, the substrate film includes a PO film. In some embodiments of the present application, the substrate film includes a PO film.
[0027] In some embodiments of the present application, the UV viscosity-reducing adhesive does not include a reactive diluent or a reactive monomer. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0030] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0031] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0032] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0033] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0034] UV adhesive tape is a tape that has high adhesion before light exposure, but greatly reduces adhesion after light exposure. It is widely used in medical, display, semiconductor and other fields due to its excellent transparency and adhesion. After a short period of light exposure, an interpenetrating polymer network structure is formed inside the UV adhesive tape. This structure changes the fluidity, cross-linking density, free volume and surface energy of the system, thereby reducing the adhesiveness and peeling strength of the tape.
[0035] In recent years, with the development of semiconductor cutting and cutting of hard materials such as glass and substrates, new demands have been put forward for UV anti-viscosity tapes. For example, UV anti-viscosity tapes need to have a higher adhesion (for example, greater than 35N / 25mm) during cutting or use (that is, before UV irradiation) and not detach from the base film. However, existing UV anti-viscosity tapes have the problem of unsatisfactory adhesion before UV irradiation or detachment from the base film.
[0036] In view of this, an embodiment of the present application provides a UV viscosity-reducing adhesive, which includes an acrylate resin. Specifically, by mass, the synthetic raw materials of the acrylate resin include a soft monomer, a hard monomer, and a functional monomer; the functional monomer includes hydroxyethyl acrylate, acrylamide, and acrylic acid; wherein the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9).
[0037] In the embodiment of the present application, a new acrylate resin is prepared, and the materials for synthesizing the acrylate resin include soft monomers, hard monomers, hydroxyethyl acrylate, acrylamide and acrylic acid, and the hydroxyethyl acrylate: acrylamide: acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9). The UV viscosity-reducing adhesive including the acrylate resin in the embodiment of the present application has a high adhesion (for example, greater than 35N / 25mm) and does not separate from the base film (that is, does not debond).
[0038] It is understandable that the soft monomer in the embodiment of the present application usually has a lower glass transition temperature (Tg), which can improve the toughness and flexibility of the resin; the hard monomer generally has a higher glass transition temperature, which increases the hardness and heat resistance of the resin; the functional monomer usually carries a special chemical functional group, which is used to give the resin specific properties, such as chemical resistance, UV stability or adhesion. It should be noted that although the main functions of the soft monomer, hard monomer and functional monomer in the acrylic resin are different, the joint action of the soft monomer, hard monomer and functional monomer affects the performance of the entire acrylic resin, and the selection and ratio of different soft monomers, hard monomers and functional monomers make the overall performance of the acrylic polymer different. In the present application, by adding a specific component and content of functional monomers to the raw materials for synthesizing the acrylic resin, the soft monomer and the hard monomer are combined to improve the adhesion of the UV viscosity-reducing tape with the acrylic resin of the embodiment of the present application, and there is no problem of degumming. In some embodiments of the present application, the soft monomer includes at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate and ethyl acrylate.
[0039] In some embodiments of the present application, the hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile.
[0040] In some embodiments of the present application, the functional monomer includes at least one of hydroxyethyl acrylate, acrylic acid, β-acryloxypropionic acid, glycidyl methacrylate, and acrylamide.
[0041] In some embodiments of the present application, the synthetic raw materials of the acrylic resin also include an initiator. By mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid: the initiator is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9): (0.01-0.05).
[0042] It should be noted that the initiator in the present application is not particularly limited. For example, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, ammonium persulfate, and the like.
[0043] In some embodiments of the present application, the weight average molecular weight of the acrylic resin is 350000 g / mol to 750000 g / mol. Further, the weight average molecular weight of the acrylic resin is 500000 g / mol to 750000 g / mol. This is conducive to increasing the adhesion of the UV anti-viscosity tape with the acrylic resin.
[0044] The present invention also provides a method for preparing an acrylic resin, comprising the following steps:
[0045] Step (11) introducing protective gas into the reaction container.
[0046] Specifically, the reaction container is a five-necked flask, the protective gas is nitrogen, and the ventilation time is 5 min to 60 min.
[0047] Step (12) Add part of the monomer raw material into the reaction container and heat it to 65° C. to 70° C. to obtain a first reaction solution.
[0048] Specifically, a portion of the soft monomer, the hard monomer and the functional monomer are weighed and dissolved in the solvent A as a base material, added into a five-necked flask, and the stirrer is turned on and the temperature is increased.
[0049] Step (13) The first reaction solution obtained in step (12) is further heated to 70° C. to 75° C., and the remaining monomer raw materials and a portion of the initiator are added and reacted for 1 to 2 hours to obtain a second reaction solution.
[0050] Specifically, after the first reaction liquid is heated up, the remaining monomer raw materials (ie, soft monomers, hard monomers and functional monomers) and a portion of the initiator are dissolved in solvent A, and slowly added to the flask using a peristaltic pump. After the addition is completed, the reaction is carried out for about 1.5 hours to obtain the second reaction liquid.
[0051] Step (14) The second reaction liquid obtained in step (13) is further heated to 75° C. to 85° C., and the remaining initiator is added, and the reaction is continued until the monomer raw materials react completely, and then heating is stopped to obtain an acrylate resin for use.
[0052] Specifically, the remaining initiator is added dropwise to the second reaction liquid, and the reaction is continued for about 1.5 hours after the addition is completed. When the monomer raw materials are basically reacted, the heating is stopped to obtain the acrylic resin for use.
[0053] In some embodiments of the present application, the solid content of the acrylic resin prepared after step (14) is 35% to 50%. It should be noted that the reaction method is a solution polymerization reaction, and the solvent, as a carrier of the reaction, has a certain influence on the polymerization activity and the gel effect. When the solid content is set within the range of 35% to 50%, the polymerization reaction rate is moderate, the viscosity is moderate, the temperature is easy to control, the chain transfer effect is small, and it is convenient for subsequent use.
[0054] In some embodiments of the present application, the solvent A is not particularly limited. For example, the solvent A includes at least one of ethyl acetate, butyl acetate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate, dipropylene glycol ethyl ether acetate, and dipropylene glycol butyl ether acetate.
[0055] In some embodiments of the present application, the UV viscosity-reducing adhesive comprises, by weight: 60 to 80 parts of acrylate resin; 18 to 38 parts of polyurethane oligomer; 0.5 to 1 part of thermal curing agent; and 0.8 to 1.8 parts of photoinitiator. The acrylate resin is specifically described above and is not further limited here.
[0056] In some embodiments of the present application, the thermal curing agent is selected from one or more of an isocyanate curing agent and an amine curing agent. Further, the thermal curing agent is preferably an isocyanate curing agent.
[0057] Specifically, the isocyanate curing agent is selected from any one or more combinations of 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0058] Specifically, the amine curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, and polyethylenepolyamine.
[0059] In some embodiments of the present application, the photoinitiator is at least one of acetophenone, dibenzoyl ketone, benzil ketal, benzophenone, 1-hydroxy-cyclohexyl benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, and the like.
[0060] It should be noted that the polyurethane oligomers in the embodiments of the present application can be purchased directly, EBECRYL8311 or EBECRYL204 (Cytec) or CN968 or CN9013NS (Sartomer), or can be prepared by oneself, which is not limited here.
[0061] In some embodiments of the present application, the new polyurethane oligomers, by mass, the raw materials for synthesizing the polyurethane oligomers include: 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of propylene hydroxy ester, 0.04 to 0.08% of catalyst, 0.04 to 0.08% of inhibitor. Adding the polyurethane oligomers prepared in the embodiments of the present application to the UV viscosity-reducing adhesive is beneficial to further improve the adhesion of the UV viscosity-reducing adhesive before illumination and improve the problem of residual adhesive after illumination.
[0062] In some embodiments of the present application, the polyurethane oligomer has multiple functionalities.
[0063] In some embodiments of the present application, the weight average molecular weight of the polyurethane oligomer is between 900 g / mol and 3000 g / mol.
[0064] Furthermore, the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and the like.
[0065] Further, the diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol. Exemplarily, the diol is polyethylene glycol 200. Polyethylene glycol 200 has good solubility in most solvents and low cost, which is conducive to reducing the preparation cost of polyurethane oligomers.
[0066] Furthermore, the hydroxy acrylate is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, trimethylolpropane diacrylate, pentaerythritol triacrylate and the like.
[0067] In some embodiments of the present application, the catalyst is selected from at least one of triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, zinc naphthenate, etc. Exemplarily, the catalyst is dibutyltin laurate. It should be noted that in the presence of dibutyltin laurate, the hydroxyl groups on the polyethylene glycol will preferentially react with the secondary aliphatic isocyanate groups on the diisocyanate, and the remaining isocyanate groups will react with the hydroxyl groups in the hydroxy acrylate, so as to ensure the successful chain extension of the reaction and obtain the polyurethane oligomer.
[0068] In some embodiments of the present application, the polymerization inhibitor is not particularly limited, such as at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.
[0069] In some embodiments of the present application, the steps of preparing the polyurethane oligomer include:
[0070] In step (21), diisocyanate, catalyst and solvent B are first added into a reaction kettle, and then diol is slowly added dropwise for 1.5 to 3 hours. After the addition is complete, the reaction is kept warm for 0.5 to 2 hours, and the reaction temperature is controlled at 40 to 50°C.
[0071] Step (22) continues to drip hydroxy acrylate and polymerization inhibitor into the reaction kettle for 0.5 to 1 hour. After the dripping is completed, the reaction is kept warm for 5 to 10 hours. The temperature of the reaction is increased to 50 to 65° C., the reaction is detected to be complete, and the temperature is lowered and the material is discharged.
[0072] In some embodiments of the present application, in step (22), the detection method is: taking the reaction solution for infrared analysis, if there is no 2240cm -1 If a peak appears near the reaction solution, the reaction is considered complete, or the reaction solution is taken for -NCO value titration. If the titration result is ≤0.5%, the reaction is considered complete.
[0073] In some embodiments of the present application, the solid content of the polyurethane oligomer prepared in step (22) is 40% to 60%. It should be noted that the reaction method is also a solution polymerization reaction, and the solvent, as a carrier of the reaction, has a certain influence on the polymerization activity and gel effect. When the solid content is set within the range of 40 to 60%, the polymerization reaction rate is moderate, the viscosity is moderate, and the temperature is easy to control.
[0074] In some embodiments of the present application, the solvent B is not particularly limited and may be at least one of ethyl acetate, butyl acetate, acetone, butanone, etc.
[0075] The present application also provides a method for preparing a UV adhesive tape, comprising the following steps:
[0076] Step (31) provides UV viscosity-reducing adhesive solution.
[0077] Specifically, UV viscosity-reducing adhesive is added into a container, solvent C is added to adjust the viscosity, mixed evenly, and allowed to stand for defoaming to obtain adhesive solution.
[0078] Specifically, the solvent C is not particularly limited. For example, the solvent C includes at least one of ethyl acetate, butyl acetate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate, dipropylene glycol ethyl ether acetate, dipropylene glycol butyl ether acetate, etc. It should be noted that the solvent A and the solvent C may be the same or different, and are not limited here.
[0079] Step (32) is to coat the UV viscosity reducing adhesive solution on the release film.
[0080] Specifically, a coating machine is used to evenly coat the adhesive on the release film. Exemplarily, the release film is PET.
[0081] Step (33) dries the release film coated with the UV viscosity reducing adhesive solution.
[0082] Specifically, the release film coated with UV viscosity-reducing adhesive is placed in an oven to dry the solvent at a temperature of 60 to 100° C. for 1 to 3 minutes, and then coated on the substrate film to obtain an adhesive tape. Exemplarily, the substrate film is one of EVA, PET, PO, and PVC, and more preferably, the substrate film is PO.
[0083] Step (34) is to put the above-mentioned tape into an oven for curing at a temperature of 40 to 70° C. for 24 to 72 hours. After curing is completed, a high peel strength UV anti-adhesive tape is obtained.
[0084] In some embodiments of the present application, the viscosity of the UV viscosity-reducing adhesive is 300 to 3000 cps, and more preferably, the viscosity is 500 to 1500 cps.
[0085] In some embodiments of the present application, the dry thickness of the adhesive layer is 10 to 30 um, and more preferably, the dry thickness of the adhesive layer is 15 um.
[0086] In some embodiments of the present application, the 180° peel strength of the UV-resistant adhesive tape at room temperature can reach more than 40N / 25mm, and the 180° peel strength after UV treatment is reduced to less than 0.3N / 25mm.
[0087] The UV adhesive tape in this application is further described below in conjunction with specific examples and experimental data.
[0088] Acrylate resin example 1 (Z11)
[0089] (1) Preparation of acrylic resin
[0090] Step 111: nitrogen was introduced into a five-necked flask for 30 min.
[0091] Step 112: 20.4 g of isooctyl acrylate, 6.9 g of methyl acrylate, 0.3 g of hydroxyethyl acrylate, 0.3 g of acrylamide, and 2.1 g of acrylic acid were dissolved in 60 g of ethyl acetate as a base material, added to a five-necked flask, stirred, and heated to 70° C. Then, 47.6 g of isooctyl acrylate, 16.1 g of methyl acrylate, 0.7 g of hydroxyethyl acrylate, 0.7 g of acrylamide, 4.9 g of acrylic acid, 0.1 g of azobisisobutyronitrile, and 30 g of ethyl acetate were slowly added dropwise, and the mixture was reacted for 3 hours after the addition was completed.
[0092] Step 113: Raise the temperature to 75° C., slowly drop 0.06 g of azobisisobutyronitrile and 30 g of ethyl acetate into the reaction bottle, and react for 1.5 hours after the dropwise addition.
[0093] Step 114: Raise the temperature to 80°C, slowly drop 0.04g of azobisisobutyronitrile and 30g of ethyl acetate into the reaction bottle, react for 1.5h after the dropwise addition, and cool the material to obtain acrylate resin for standby use. The acrylate resin has a solid content of 38%. The weight average molecular weight of the acrylate resin is 516000g / mol, and the glass transition temperature of the acrylate resin is -37°C.
[0094] Acrylate resin example 2 (Z12)
[0095] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 1.5:1.5:6. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 613000 g / mol, and the glass transition temperature of the acrylic resin is -40°C.
[0096] Acrylate resin example 3 (Z13)
[0097] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 61:30:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 599000 g / mol, and the glass transition temperature of the acrylic resin is -30°C.
[0098] Acrylate resin example 4 (Z14)
[0099] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 65:25:10 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:9. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 726000 g / mol, and the glass transition temperature of the acrylic resin is -27°C.
[0100] Acrylate resin example 5 (Z15)
[0101] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 553000 g / mol, and the glass transition temperature of the acrylic resin is -15°C.
[0102] Acrylate resin example 6 (Z16)
[0103] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 702000 g / mol, and the glass transition temperature of the acrylic resin is -28°C.
[0104] Acrylate resin comparative example 1 (D11)
[0105] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate and acrylic acid) is 68:23:9; among which, the ratio of hydroxyethyl acrylate: acrylic acid is 1:8.
[0106] Acrylate resin comparative example 2 (D12)
[0107] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (acrylamide and acrylic acid) is 68:23:9; wherein the ratio of acrylamide: acrylic acid is 1:8.
[0108] Acrylate resin comparative example 3 (D13)
[0109] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9; among which, the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 5:0.5:3.5.
[0110] Acrylate resin comparative example 4 (D14)
[0111] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9; among which, the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:5:3.5.
[0112] Polyurethane oligomer example 1 (Z21)
[0113] Step 121: First add 34.2g of diphenylmethane diisocyanate, 0.05g of triethanolamine and 12.415g of acetone into a reaction kettle, and then slowly add 15.4g of polyethylene glycol 200 and 30g of acetone dropwise for 1.5h. After the addition is complete, keep the reaction warm for 1h and control the reaction temperature at 45°C.
[0114] Step 122: Continue to drop 50.4 g of pentaerythritol triacrylate, 0.03 g of toluene diphenol and 15 g of acetone into the reactor for 0.5 h. After the addition is complete, heat to 60 °C and keep warm for 6 h. The reaction liquid has no 2240 cm -1 The peak is discharged near the mol / l, and the material is discharged after cooling to obtain a polyurethane oligomer for use. The weight average molecular weight of the prepared polyurethane oligomer is 980 g / mol, and the double bond content is 0.54 mol / 100 g.
[0115] Polyurethane oligomer example 2 (Z22)
[0116] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 39.8:17.9:42.2; wherein the hydroxy acrylate includes pentaerythritol triacrylate and hydroxypropyl acrylate, and the ratio of pentaerythritol triacrylate: hydroxypropyl acrylate is 19.67:8.59. The weight average relative molecular mass of the prepared polyurethane oligomer is 910 g / mol, and the double bond content is 0.38 mol / 100 g.
[0117] Polyurethane oligomer example 3 (Z23)
[0118] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 36.8:16.5:46.6; wherein the hydroxy acrylate includes pentaerythritol triacrylate and hydroxypropyl acrylate, and the ratio of pentaerythritol triacrylate: hydroxypropyl acrylate is 29.53:4.29. The weight average molecular weight of the prepared polyurethane oligomer is 950 g / mol, and the double bond content is 0.47 mol / 100 g.
[0119] Polyurethane oligomer example 4 (Z24)
[0120] The difference between the polyurethane oligomer and Example 1 is that, by mass, diphenylmethane diisocyanate is used to replace isophorone diisocyanate, and the ratio of diphenylmethane diisocyanate: polyethylene glycol 200: hydroxy acrylate is 36.9:14.7:48.3; wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 977 g / mol, and the double bond content is 0.57 mol / 100 g.
[0121] Polyurethane oligomer example 5 (Z25)
[0122] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 31.7:21.4:46.8, wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 1100 g / mol, and the double bond content is 0.51 mol / 100 g.
[0123] Polyurethane oligomer Example 6 (Z26)
[0124] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 35.4:15.9:48.5, wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 1050 g / mol, and the double bond content is 0.58 mol / 100 g.
[0125] Preparation of UV viscosity-reducing tape: Prepare UV viscosity-reducing adhesive liquid according to the raw material composition and ratio in Table 1. The specific process is: add acrylate copolymer, polyurethane oligomer, thermal curing agent, photoinitiator 1173 and appropriate amount of ethyl acetate into a cup according to a certain ratio, mix evenly, the viscosity is 1200cps, and stand to defoam. Use a coating machine to evenly coat the above UV viscosity-reducing adhesive liquid on the PET release film. Put it in an oven at 80℃ / 2min to dry the solvent, and then transfer it to the substrate film to obtain a tape. Then put the tape in an oven and cure it at 40℃ for 72h to obtain a UV viscosity-reducing tape.
[0126] Table 1
[0127]
[0128]
[0129]
[0130] Experimental test:
[0131] Peel strength test before / after illumination: The test standard is GB / T2792-2014. The specific operation is to cut a 25mmx300mm tape sample and use a universal material testing machine to perform a 180° peel strength test.
[0132] Test whether it is detached from the base film under stretching conditions: visual inspection, the specific operation is to cut a 10mmx100mm sample, use a universal material testing machine, set the initial spacing to 50mm, the stretching speed to 200mm / min, stretch the sample to break, and observe whether there is debonding.
[0133] Residual adhesive test after light exposure: visual inspection, the specific operation is to observe whether there is any residual material on the substrate after the peeling force is measured after light exposure.
[0134] The UV adhesive tapes prepared in each experimental example in Table 1 were subjected to a peel strength test before illumination, a test on whether they were detached from the base film under stretching conditions, and a test on residual adhesive after illumination. The test results are shown in Table 2.
[0135] Table 2
[0136]
[0137]
[0138] It can be seen from Examples 1 to 14 of the UV adhesive tape and Comparative Examples 1 to 4 that adding the acrylic resin prepared in the examples of the present application to the UV adhesive tape is beneficial to improving the peel strength of the UV adhesive tape before light exposure. Although the UV adhesive tape prepared in Comparative Example 4 has a much higher adhesive strength before light exposure than Comparative Example 1, it has the problem of separation of the adhesive layer from the substrate during the stretching process.
[0139] It can be seen from Examples 1 to 13 and Example 14 that the UV anti-viscosity tape prepared by combining the acrylic resin and polyurethane polymer prepared in the examples of the present application can further solve the problem of residual adhesive in the UV anti-viscosity tape after irradiation with light, that is, the obtained UV anti-viscosity tape has a high peel strength before irradiation and a very low peel strength after irradiation with light. At the same time, it will not demold under stretching conditions and will not produce residual adhesive after irradiation with light.
[0140] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. An acrylate resin, characterized in that The synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers by mass; the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid; Among them, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9).
2. The acrylic resin according to claim 1, characterized in that The functional monomers are composed of hydroxyethyl acrylate, acrylamide and acrylic acid; and / or The synthetic raw materials of the acrylic resin also include an initiator. By mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid: the initiator is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9): (0.01-0.05).
3. The acrylate resin according to claim 1, characterized in that The glass transition temperature of the acrylic resin is -40 to -15°C; and / or The relative molecular mass of the acrylic resin is 3500000-700000 g / mol; and / or The solid content of the acrylic resin is 35-50%.
4. The acrylate resin according to claim 2, characterized in that The soft monomer comprises at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate and ethyl acrylate; and / or The hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile; and / or The initiator comprises at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, diisopropyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, and ammonium persulfate.
5. An acrylic resin, characterized in that: The molecular chain structure of the acrylic resin includes a soft monomer structural unit, a hard monomer structural unit and a functional monomer structural unit. The functional monomer structural unit includes a hydroxyethyl acrylate structural unit, an acrylamide structural unit and an acrylic acid structural unit. By mass, the soft monomer structural unit: the hard monomer structural unit: the hydroxyethyl acrylate structural unit: the acrylamide structural unit: the acrylic acid structural unit is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9).
6. A method for preparing an acrylic resin, characterized in that: The preparation method comprises the following steps: Passing protective gas into the reaction vessel; Add part of the monomer raw material into the reaction container, and heat it to 65-70° C. to obtain a first reaction solution; The first reaction liquid is further heated to 70-75° C., and the remaining monomer raw materials and a portion of the initiator are added and reacted for 1 to 2 hours to obtain a second reaction liquid; The second reaction liquid is further heated to 75-85° C., and the remaining initiator is added to obtain an acrylic resin after the monomer raw materials react. The monomer raw materials include soft monomers, hard monomers and functional monomers. The functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid. By mass, the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid: the initiator is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9): (0.01-0.05).
7. The preparation method according to claim 6, characterized in that: The soft monomer comprises at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate and ethyl acrylate; and / or The hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile; and / or The initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, diisopropyl peroxide, diisopropyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, and ammonium persulfate.
8. A UV anti-adhesive tape, characterized in that: The UV anti-viscosity tape comprises the acrylate resin according to any one of claims 1 to 5 or the acrylate resin obtained by the preparation method according to claim 6 or 7.
9. The UV adhesive tape according to claim 8, characterized in that: The UV anti-viscosity tape comprises a substrate film and a UV anti-viscosity adhesive on the substrate film, wherein the UV anti-viscosity adhesive comprises an acrylate resin, a thermal curing agent, a photoinitiator and a polyurethane polymer, wherein by mass, the acrylate resin: the polyurethane polymer: the thermal curing agent: the photoinitiator is (60 to 80): (18 to 38): (0.5 to 1): (0.8 to 1.8).
10. The UV adhesive tape according to claim 9, characterized in that: The substrate film includes a PO film; and / or the UV viscosity-reducing adhesive does not include a reactive diluent or a reactive monomer.